Skeletal, soft tissue, and airway changes following the alternate maxillary expansions and constrictions protocol - (:unkn) unknown (E H ANGLE EDUCATION RESEARCH FOUNDATION, INC, 2015)
Objective: To evaluate the skeletal, soft tissue, and airway effects of the alternate maxillary expansions and constrictions (Alt-RAMEC) protocol in prepubertal patients. Materials and Methods: The appliance containing a double-hinged expansion screw was applied to 20 patients with Class III skeletal malocclusion characterized by maxillary retrognathia. The mean age of the study group was 9 years and 8 months. The patients' parents were instructed to open the screw by 1 mm per day during the first week and to close it by 1 mm per day the week after. This alternate opening and closing was repeated for 9 consecutive weeks. Cone beam computed tomography records and three-dimensional photographs were taken before treatment and after 9 week of the Alt-RAMEC protocol. Results: Point A moved slightly forward (0.89 mm) and downward (0.92 mm) (P < .05). The average amount of expansion achieved at the level of point A was 5.54 mm (P < .05). Besides the maxilla, the expansive forces also affected the nasal bone, the zygomaticomaxillary and zygomaticotennporal sutures (P < .05). The soft tissue nasal width increased significantly. The airway volume of the anterior nasal compartment and the nasal cavity also increased (P < .05). Conclusions: Slight forward movement of point A occurred with the Alt-RAMEC protocol. The expansion affected not only the maxilla but also other structures of the face. Significant cutaneous changes occurred in the paranasal area. Some significant increase in the upper airway volume was obtained.
Keywords: Alt-RAMEC; Double-hinged expansion screw; Class III malocclusion; Airway; BEAM COMPUTED-TOMOGRAPHY; RAPID PALATAL EXPANSION; PHARYNGEAL AIRWAY; DIMENSIONS; PROTRACTION